Petite idole énigmatique aux yeux allongés et pleins de rêve ». Les stéréotypes orientalistes dans Le Harem entr’ouvert d’A.-R. de Lens - Sokołowicz, Małgorzata (Romanica Silesiana, 2021)
The present paper describes some orientalist stereotypes concerning women and manifesting themselves in Le Harem entr’ouvert (1919), a short story collection by Aline Réveillaud de Lens (1881–1925), a French painter and writer, whose works are devoted mainly to North Africa. The paper focuses on three, most common, stereotypical representations of the Oriental woman according to which she is, firstly, a beautiful odalisque serving the man; secondly, extremely sensual and thus unfaithful and, finally, jealous and, sometimes, very cruel. The author attempts to explain the origins of those representations and to answer the question why A.-R. de Lens used them in her writings